IMPROVEMENT OF THE SERVICE SYSTEM IN AGRICULTURE - Musaeva Nigora Nuriddinovna (Web of Journals Publishing, 2024)
This article discusses the enhancement of the agricultural service system, emphasizing the need for technological integration, better training for service personnel, and sustainable practices. The study analyzes existing literature, identifies gaps, and proposes methods to boost efficiency and resilience in agricultural services. Results demonstrate that improved service delivery can lead to increased productivity, reduced environmental impact, and economic growth.
Keywords: Agriculture, service system, technology integration, sustainable practices, productivity, service efficiency.